Association between long working hours and sleep problems in white‐collar workers - NAKASHIMA, MOTOKO; MORIKAWA, YUKO; SAKURAI, MASARU; NAKAMURA, KOSHI; MIURA, KATSUYUKI; ISHIZAKI, MASAO; KIDO, TERUHIKO; NARUSE, YUCHI; SUWAZONO, YASUSHI; NAKAGAWA, HIDEAKI (Journal of sleep research, 2011)
Summary The purpose of this study is to examine the association between long work hours and sleep disturbance among white‐collar workers. We evaluated 1510 male white‐collar full‐time employees, between the ages of 18 and 59 years, using a comprehensive sleep quality questionnaire, the Pittsburgh Sleep Quality Index (PSQI). All subjects worked in a light metal products factory in Japan. The mean number of monthly overtime work hours was determined using data from the previous 6 months from timecard records. Subjects were divided into five groups based on quintiles of the mean number of monthly overtime work hours: <26 h month−1; ≥26 but <40; ≥40 but <50; ≥50 but <63; and >63. Leisure time physical activity, drinking habits just before sleep, presence of family/partner and health status were used as confounding factors in the multiple regression model. The prevalence of short sleep hours, impairment of sleep efficiency and daytime dysfunction among seven components of PSQI increased, in a dose–response relationship, with overtime work hours. The prevalence of high global score (>5.5 points) was highest in workers with overtime hours ≥50 h week−1. The odds ratios after adjustment for confounding factors for high global score using less than 26 h as a reference group were 1.67 for workers with ≥50 h and <63 h, and 1.87 for workers with 63 h and more. To conclude, the present results suggest that long work hours correlate with reduced sleep quality in a dose–response manner.